Contemporary realism, and modernity in the northern mexican border cinema (English version) - Alba Nidia Sánchez Baltazar (Ñawi: Arte, Diseño y Comunicación)
Based on the review of the strategies of realism and modern cinema, and from the analysis of the film La Paloma y el Lobo (2019) directed by Carlos Lenin, this essay seeks to investigate the role played by the cinema of Mexico's northern border in understanding both the current contextual conditions of the region, as well as the historical evolution to which the border has been subjected since the establishment of neoliberalism in the country.